ANALYSIS OF PHUBBING BEHAVIOR AS A FACTOR OF DECREASE IN ADOLESCENT SOCIAL INTERACTION: A CASE STUDY IN KARANG REJO GANG - Nadila Nadila; Muhammad Putra Dinata Saragi (SOSIOEDUKASI, 2025)
The development of communication technology has significantly transformed adolescents’ patterns of social interaction, one of which is reflected in the phenomenon of phubbing, namely the tendency to ignore interlocutors due to excessive focus on smartphones. This study aims to analyze the forms of phubbing behavior and its impact on the quality of social interactions among adolescents in Gang Karang Rejo, Medan City. This research employed a descriptive qualitative approach using a purposive sampling technique involving five adolescents aged 14–18 years as the main informants, with parents serving as supporting informants. The data were collected through in-depth interviews, non-participatory observation, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing, followed by verification using source and method triangulation. The results indicate that phubbing has become a normalized daily habit among adolescents, characterized by frequent smartphone use during interactions, repetitive checking of notifications, feelings of anxiety when separated from the device, and decreased focus during face-to-face communication. This behavior negatively affects the quality of social interactions, as seen in reduced empathy, weakened emotional closeness with family members, and the loss of togetherness during social encounters. The discussion highlights that phubbing is no longer an individual behavior but has developed into a broader social phenomenon that shapes the relational dynamics of adolescents within their families and communities, suggesting the need for educational strategies, parental guidance, and controlled smartphone use to maintain a balanced integration of digital and face-to-face interactions.